2018
DOI: 10.1002/wcs.1483
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for interpreting the Language Familiarity Effect in talker processing

Abstract: The Language Familiarity Effect (LFE)—where listeners are better at processing talker‐voice information in their native language than in an unfamiliar language—has received renewed attention in the past 10 years. Numerous studies have sought to probe the underlying causes of this advantage by cleverly manipulating aspects of the stimuli (using phonologically related languages, backwards speech, nonwords) and by examining individual differences across listeners (testing reading ability and pitch perception). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
(242 reference statements)
0
12
0
Order By: Relevance
“…For example, language familiarity facilitates vocal emotion detection (Pell & Skorup, ; Scherer, Banse, & Wallbott, ), consonant and vowel perception is influenced by talker identity (Eisner & McQueen, ; Johnson, Strand, & Johnson, ), talker familiarity enhances word recognition in adverse listening conditions (Creel, Aslin, & Tanenhaus, ; Goldinger, ; Mullennix & Pisoni, ; Nygaard, Sommers, & Pisoni, ), and certain speech sounds carry more information about talker identity than others (Andics, McQueen, & van Turennout, ; Cutler, Andics, & Fang, ). Most importantly for this study, adults recognize talkers better in a familiar language than in an unfamiliar language, a phenomenon known as the language familiarity effect (Goggin, Thompson, Strube, & Simental, ; Johnson, Bruggeman, & Cutler, ; Levi, ; Orena, Theodore, & Polka, ; Perrachione, ).…”
mentioning
confidence: 86%
“…For example, language familiarity facilitates vocal emotion detection (Pell & Skorup, ; Scherer, Banse, & Wallbott, ), consonant and vowel perception is influenced by talker identity (Eisner & McQueen, ; Johnson, Strand, & Johnson, ), talker familiarity enhances word recognition in adverse listening conditions (Creel, Aslin, & Tanenhaus, ; Goldinger, ; Mullennix & Pisoni, ; Nygaard, Sommers, & Pisoni, ), and certain speech sounds carry more information about talker identity than others (Andics, McQueen, & van Turennout, ; Cutler, Andics, & Fang, ). Most importantly for this study, adults recognize talkers better in a familiar language than in an unfamiliar language, a phenomenon known as the language familiarity effect (Goggin, Thompson, Strube, & Simental, ; Johnson, Bruggeman, & Cutler, ; Levi, ; Orena, Theodore, & Polka, ; Perrachione, ).…”
mentioning
confidence: 86%
“…Indeed, it has been shown that listeners can use fine-grained phonetic information, such as VOT, to identify talkers (Allen and Miller 2004). Additionally, work on talker identification has consistently shown a Language Familiarity Effect (LFE), i.e., listeners are better at identifying talkers in their native language (e.g., Fleming et al 2014;Goggin et al 1991;Perrachione et al 2011;Thompson 1987;Levi 2019). For example, Goggin et al (1991) showed that monolingual English listeners were better at identifying English voices than German ones, and German listeners exhibited the opposite pattern.…”
Section: Literature Review 21 Identifying Accents and Talkersmentioning
confidence: 99%
“…Nevertheless, if listeners are not able to link the neofalantes' accent with the sociolinguistic label, whether they classify neofalantes as Spanish-dominant or Galician-dominant speakers would be informative of whether neofalantes' speech production patterns have changed after the language dominance switch. Language ability, language familiarity and attunement to the phonological system have been shown to be beneficial for talker identification (Fleming et al 2014;Goggin et al 1991;Johnson et al 2018;Levi 2019;Perrachione et al 2011;Thompson 1987) and experience with a particular variety appears to enhance the accuracy of identification of that variety (Clopper andPisoni 2004, 2006). If accent categorisation ability relies on similar mechanisms to talker identification skills, it might be influenced by similar factors.…”
mentioning
confidence: 99%
“…English listeners recognizing English speakers) than speakers of an unfamiliar language (e.g., English speakers [16]). Two models have been proposed to explain the language familiarity effect [17,18]: the phonetic familiarity model, which argues that listeners rely on their familiarity with the statistical distribution of phonetic features in their native language, and the linguistic processing model, which argues that listeners also incorporate higher-level information, such as word recognition and comprehension.…”
Section: Talker Recognition (By Humans)mentioning
confidence: 99%